2009
DOI: 10.1136/jech.2008.081141
|View full text |Cite
|
Sign up to set email alerts
|

Black-white differences in avoidable mortality in the USA, 1980-2005

Abstract: There is considerable potential for narrowing of the black-white difference in AM, especially from causes amenable to medical care and (for men) policy/behaviour interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 62 publications
2
43
0
1
Order By: Relevance
“…This analysis has been at the country level only and has not disaggregated mortality by region, ethnicity or socioeconomic characteristics, so concealing potentially large variations within populations [3]. Evidence from Australia, New Zealand and the United States consistently points to higher levels of amenable mortality among, respectively, the indigenous population and African Americans compared to non-indigenous populations and white Americans [22][23][24]. In the US however the gap varies substantially by state [25], suggesting that observed differences cannot solely be attributed to lifestyle or biological factors.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis has been at the country level only and has not disaggregated mortality by region, ethnicity or socioeconomic characteristics, so concealing potentially large variations within populations [3]. Evidence from Australia, New Zealand and the United States consistently points to higher levels of amenable mortality among, respectively, the indigenous population and African Americans compared to non-indigenous populations and white Americans [22][23][24]. In the US however the gap varies substantially by state [25], suggesting that observed differences cannot solely be attributed to lifestyle or biological factors.…”
Section: Discussionmentioning
confidence: 99%
“…Race-based mortality disparities have been documented among nonHispanic black adults [1][2][3][4] and American Indian and Alaska Native populations, 5,6 although Hispanic adults generally do not differ from whites. [7][8][9] Excess mortality-generally death that occurs before a person reaches average life expectancy-has also been found among residents of nonmetropolitan US counties, [10][11][12][13] although some rural communities differ from this trend.…”
mentioning
confidence: 99%
“…To be sure, investigators have extensively studied the racial/ethnic disparities that persist despite overall gains in life expectancy and in specific health indicators in the last 15 years. [25][26][27][28][29] However, to our knowledge, health scholars have not investigated the different trajectories of city distress as a factor explaining health disparities and urban health. Several influential studies have demonstrated that health disparities exist between Blacks and Whites within cities, [30][31][32] and that the health of Blacks in cities is worse than that of Blacks in rural areas.…”
mentioning
confidence: 99%